The Staphylococcus aureus Opp1 ABC transporter imports nickel and cobalt in zinc‐depleted conditions and contributes to virulence. Issue 4 (23rd December 2012) - Remy, Laetitia; Carrière, Marie; Derré‐Bobillot, Aurélie; Martini, Cécilia; Sanguinetti, Maurizio; Borezée‐Durant, Elise
Summary: Metals are common enzymatic cofactors, and their acquisition must be assured under the various conditions encountered in the host. Although some strategies for acquisition of common metals such as iron and manganese have been elucidated, little is known about the conditions and mechanisms used to capture trace metals. Nickel is a transition metal required as a cofactor for several bacterial enzymes, including urease. Staphylococcus aureus does express a nickel ABC transporter, Nik, which functions in metal‐replete medium and is necessary for nickel urease activity and urinary tract colonization. In this work, we identified a novelc obalt andn ickelt ransporter, which we named Cnt (previously annotated Opp1), in the major opportunistic pathogen S. aureus . Metal transport activity was revealed by growing cells in a chemically defined medium devoid of metals. Zinc specifically inhibits Cnt‐mediated nickel and cobalt uptake, on both functional and transcriptional levels. Mortality due to S. aureus cnt mutant in systemic infection and colonization of the bladder and kidneys in ascending urinary tract infection model were reduced compared to the parent strain. This study identifies a novel S. aureus trace metal transporter and its restricted conditions of activity, and establishes its role in infection.